2001
DOI: 10.4049/jimmunol.167.9.5375
|View full text |Cite
|
Sign up to set email alerts
|

Novel Small Molecule Inhibitor of C1s Exerts Cardioprotective Effects in Ischemia-Reperfusion Injury in Rabbits

Abstract: Myocardial ischemia-reperfusion injury can be related to complement activation with generation of chemotactic agents, adhesion molecule expression, release of cytokines and oxygen-derived free radicals, and subsequent neutrophil accumulation. In the present study the cardioprotective effects of a novel highly selective small molecule C1s inhibitor (C1s-INH-248, Knoll) were examined in a rabbit model of myocardial ischemia (I) and reperfusion (R; i.e., 60 min I + 180 min R). In in vitro tests (enzyme activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 33 publications
2
42
0
4
Order By: Relevance
“…Chronic intermittent hypoxia/reoxygenation is characteristic of CIH, and several studies support the notion that complement activation is involved in the pathogenesis of hypoxia/reoxygenation injury, and that complement inhibition reduces the extent of injury (5,8,9). In support of this hypothesis, studies have demonstrated that the localization/deposition of complement components (such as C1q, C3, C4 and C5) occurs in hypoxic myocardium (10)(11)(12)(13).…”
Section: Discussionsupporting
confidence: 52%
“…Chronic intermittent hypoxia/reoxygenation is characteristic of CIH, and several studies support the notion that complement activation is involved in the pathogenesis of hypoxia/reoxygenation injury, and that complement inhibition reduces the extent of injury (5,8,9). In support of this hypothesis, studies have demonstrated that the localization/deposition of complement components (such as C1q, C3, C4 and C5) occurs in hypoxic myocardium (10)(11)(12)(13).…”
Section: Discussionsupporting
confidence: 52%
“…In myocardial I/R models, recent work indicates that the mannose-binding lectin, as well as the classical activation pathway, plays a role in complement activation and subsequent organ damage (22,23). Regarding the precise pathway of complement activation upon renal I/R injury much remains to be resolved, however evidence is growing that activation of the complement system plays a crucial role in the pathogenesis of renal I/R injury (5).…”
Section: Discussionmentioning
confidence: 99%
“…CRP has been shown to colocalize with complement in acute myocardial infarction (39) and together they have been demonstrated to be important mediators of the resulting tissue damage (2,36). Inhibition of the early phase of complement activation has been demonstrated in an animal model to have cardioprotective effects following ischemia/reperfusion injury (40), and using complement inhibition as a therapy is the subject of many studies (reviewed in Refs. 41 and 42).…”
Section: Discussionmentioning
confidence: 99%